2021
DOI: 10.1186/s12903-021-01417-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating saliva aerosol contamination in a dental school clinic

Abstract: Background Transmission of COVID-19 via salivary aerosol particles generated when using handpieces or ultrasonic scalers is a major concern during the COVID-19 pandemic. The aim of this study was to assess the spread of dental aerosols on patients and dental providers during aerosol-generating dental procedures. Methods This pilot study was conducted with one volunteer. A dental unit used at the dental school for general dental care was the site of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 19 publications
(26 reference statements)
7
35
0
Order By: Relevance
“…Ultrasonic scaling requires a substantial volume of cooling irrigant and as a result, this procedure was deemed to be an AGP during the early COVID-19 pandemic (Office of Chief Dental Officer England 2020). Our study in patients supports findings from phantom head studies (Allison et al 2021;Veena et al 2015) and an N-of-one human volunteer study (Yang et al 2021) that ultrasonic scaling produces mainly instrument generated aerosol. Similar to Yang et al and Allison et al, we found the quantity of aerosol produced was low in comparison to high speed drilling (at least 10 times less).…”
Section: Discussionsupporting
confidence: 88%
“…Ultrasonic scaling requires a substantial volume of cooling irrigant and as a result, this procedure was deemed to be an AGP during the early COVID-19 pandemic (Office of Chief Dental Officer England 2020). Our study in patients supports findings from phantom head studies (Allison et al 2021;Veena et al 2015) and an N-of-one human volunteer study (Yang et al 2021) that ultrasonic scaling produces mainly instrument generated aerosol. Similar to Yang et al and Allison et al, we found the quantity of aerosol produced was low in comparison to high speed drilling (at least 10 times less).…”
Section: Discussionsupporting
confidence: 88%
“…Different methods like luminescent tracer [ 43 , 56 ], particle image velocimetry [ 45 ], blacklight (LED) shadowgraph [ 46 ], microbiological analysis [ 57 ], and spectrofluorometric analysis [ 43 , 44 ] have been employed to study the spatial distribution of droplets and aerosol particles; our findings were consistent with these previous studies, despite having used a different method [ 58 , 59 ]. Our methods were able not only to characterize the risk of exposure when performing the AGPs by using the settlement patterns of the particles generated during the procedures but also to recognize potential contamination sources within a dental care setting, and to delimit critical areas for the settlement of particles.…”
Section: Discussionsupporting
confidence: 88%
“…Our ndings are consistent with those of previous studies carried out with different methods [46,47]. Our methods were able not only to characterize the risk of exposure when performing the AGPs by using the settlement patterns of the aerosol particles generated during the procedures, but also to recognize potential contamination sources within a dental care setting, and to delimit critical areas for the settlement of aerosol particles.…”
Section: Discussionsupporting
confidence: 87%